1998
DOI: 10.2527/1998.761275x
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis in cattle: a review.

Abstract: Acute and chronic acidosis, conditions that follow ingestion of excessive amounts of readily fermented carbohydrate, are prominent production problems for ruminants fed diets rich in concentrate. Often occurring during adaptation to concentrate-rich diets in feedyards, chronic acidosis may continue during the feeding period. With acute acidosis, ruminal acidity and osmolality increase markedly as acids and glucose accumulate; these can damage the ruminal and intestinal wall, decrease blood pH, and cause dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
842
11
165

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,068 publications
(1,091 citation statements)
references
References 30 publications
(46 reference statements)
32
842
11
165
Order By: Relevance
“…For example, ruminating time decreased linearly in a period of time when ruminal pH reached the nadir, from 12 to 14 h. Rumination is necessary during this time to increase saliva production, which buffers the rumen (Bailey and Balch, 1961). Meal size increased linearly during the 4 h following feeding, which may negatively affect ruminal pH and its post-prandial drop, as suggested by Allen (1997), Owens et al (1998), andCooper et al (1999). However, there is little doubt about the buffering effect of bicarbonate in the rumen (Kohn and Dunlap, 1998), which was supported in the present study by the finding that despite increasing buffer level, increased meal size during the 4 h post-feeding and drop in pH was attenuated (Gonzá lez et al, 2008).…”
Section: Drinking Behaviorsupporting
confidence: 77%
See 2 more Smart Citations
“…For example, ruminating time decreased linearly in a period of time when ruminal pH reached the nadir, from 12 to 14 h. Rumination is necessary during this time to increase saliva production, which buffers the rumen (Bailey and Balch, 1961). Meal size increased linearly during the 4 h following feeding, which may negatively affect ruminal pH and its post-prandial drop, as suggested by Allen (1997), Owens et al (1998), andCooper et al (1999). However, there is little doubt about the buffering effect of bicarbonate in the rumen (Kohn and Dunlap, 1998), which was supported in the present study by the finding that despite increasing buffer level, increased meal size during the 4 h post-feeding and drop in pH was attenuated (Gonzá lez et al, 2008).…”
Section: Drinking Behaviorsupporting
confidence: 77%
“…High proportion of concentrates in the ruminant's diets may result in physiological disorders such as ruminal acidosis, which was related to anorexia, liver abscesses, poor performance, diarrhea and lethargy (Owens et al, 1998). Ruminal buffers such as sodium bicarbonate (BICARB) have traditionally been used to improve performance and rumen health of beef cattle on these diets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after feeding diet IV, ruminal pH decreased to 5.3 on day 2 and it was maintained at about 4.7 on day 3. At the same time, goats started to reduce their feed intake on day 2 and refused to take any feed on day 3, indicating the occurrence of metabolic acidosis (Owens et al, 1998;Gentile et al, 2004). Ruminal lactic acid concentration was stable and maintained in a range of 2.71 to 3.63 mmol/l during the initial three feeding periods, but increased significantly 1 day after feeding diet IV, with a peak of 10.6 mmol/l on day 2 of feeding diet IV and then decreased (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, evidence obtained from an in vitro study in which increased WSC concentration in fresh forages were obtained by harvesting at different time of the day suggests that there may be a concentration of WSC (~24%) that optimises rumen fermentation processes (Burke et al, 2011). Owens et al (1998) suggested that the synthesis of microbial protein in the rumen may also be reduced by acidosis from feeding high level of WSC. This is partly evident from the low PD for medium high and high treatments in period 1.…”
Section: N Metabolismmentioning
confidence: 99%